CHANGES IN THE HEALTHY LIFESTYLE OF THE POPULATION OF THE FERGANA VALLEY (International journal of artificial intelligence, 2026)
This article provides a scientific and analytical examination of changes in the healthy lifestyle practices of the population of the Fergana Valley within the context of contemporary socio-economic and demographic processes. The study analyzes trends in physical activity, dietary habits, participation in preventive healthcare measures, and behavioral factors influencing public health. In addition, the role and impact of state health policies, educational institutions, and mass media in shaping healthy lifestyle awareness and practices are critically assessed. Based on the findings, key challenges are identified, and scientifically grounded conclusions and recommendations are proposed to strengthen public health and ensure the sustainable development of healthy lifestyle behaviors among the population.